Modeling strategy for clinched joints in assemblies. Issue 3 (August 2016) - Breda, A; Coppieters, S; Debruyne, D
Abstract: Clinching is a mechanical joining technique which involves severe local plastic deformation of two or more metal sheet parts resulting in a permanent mechanical interlock. Today, it is a reliable joining technique used in automotive, HVAC and general steel constructions whilst still gaining interest. As it is not computationally feasible to include detailed sub models of these type of joints in FE simulations of real-life clinched assemblies, this paper proposes a methodology to represent these connections with simplified elements. In order to calibrate the parameters governing the equivalent model, a simple shear lap and pullout test is used. This methodology is applied to clinched configurations and validated using a modified Arcan test in which both shear and pull-out loads are considered.